2014
DOI: 10.1007/s10958-014-2087-5
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocompact Primitive Topological Inverse Semigroups

Abstract: In the paper we study pseudocompact primitive topological inverse semigroups. We describe the structure of pseudocompact primitive topological inverse semigroups and show that the Tychonoff product of a family of pseudocompact primitive topological inverse semigroups is a pseudocompact topological space. Also we prove that the Stone-Čech compactification of a pseudocompact primitive topological inverse semigroup is a compact primitive topological inverse semigroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Example 1 of [6] shows that inversion on a quasi-regular inverse countably compact topological semigroup in which maximal subgroups are topological groups is not continuous. Also Corollary 3.23 and Proposition 2.8 from [17] imply that a quasi-regular primitive inverse feebly compact topological semigroup is Tychonoff. Also, Corollary 3.23 implies…”
Section: Proof Suppose For a Contradiction That There Exists An Openmentioning
confidence: 89%
See 3 more Smart Citations
“…Example 1 of [6] shows that inversion on a quasi-regular inverse countably compact topological semigroup in which maximal subgroups are topological groups is not continuous. Also Corollary 3.23 and Proposition 2.8 from [17] imply that a quasi-regular primitive inverse feebly compact topological semigroup is Tychonoff. Also, Corollary 3.23 implies…”
Section: Proof Suppose For a Contradiction That There Exists An Openmentioning
confidence: 89%
“…In the paper [17] the structure of feebly compact primitive topological inverse semigroups is described and it is shown that the Tychonoff product of an arbitrary non-empty family of feebly compact primitive topological inverse semigroups is feebly compact. Also, it is proved that the Stone-Čech compactification of a feebly compact primitive topological inverse semigroup has a natural structure of a compact primitive topological inverse semigroup.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the paper [16] it is described the structure of pseudocompact primitive topological inverse semigroups and it is shown that the Tychonoff product of an arbitrary non-empty family of pseudocompact primitive topological inverse semigroups is pseudocompact. Also, there is proved that the Stone-Čech compactification of a pseudocompact primitive topological inverse semigroup has a natural structure of a compact primitive topological inverse semigroup.…”
Section: Introductionmentioning
confidence: 99%